Childlessness, social network profiles in midlife and late adulthood, and their implications for subjective well-being - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2024)
Objectives: Despite the rising prevalence of individuals reaching advanced age without children, little is known about the diversity of support networks within childless populations. We examine the network profiles of childless adults aged 50+ in Singapore, which observes high childlessness rates despite societal emphasis on familism. Methods: We employ latent class analysis to derive network typology based on a 2022 nationwide survey in Singapore. Additionally, we use logistic regression analyses to investigate the sociodemographic correlates of childless individuals' network types and the associations between these network types and subjective well-being. Results: Childless Singaporeans form a heterogeneous group characterized by different support networks. Evidence suggests the centrality of parents in the childless' social networks and the continuity of parent-child support exchanges that extend into the child's midlife and late adulthood. When parents are absent, siblings/extended kin serve as their support sources. Age, sibship size, and socioeconomic status are key correlates of network types. Membership in diverse networks is beneficial to the subjective well-being of childless individuals. Although one-fifth of childless individuals in restricted networks demonstrate significantly poorer well-being, the remaining four-fifths show comparable, if not better, well-being than the non-childless. Discussion: Results underscore the importance of differentiating network types among the childless, particularly when assessing their well-being. Contrary to the notion of associating later-life childlessness with social isolation and vulnerabilities, many childless Singaporeans manage to construct non-child-based networks equipped with various supportive relations that cater to their needs. Nevertheless, persistent vulnerabilities among restricted network members deserve policymakers' attention.